Simplify this expression and put your answer in Scientific Notation: (5×10^6) × (2× 10^−2) explain how you got your anwser in 3 steps

3 answers

1. Multiply the coefficients: 5 * 2 = 10
2. Add the exponents: 6 + (-2) = 4
3. Put the result in scientific notation: 10 * 10^4 = 1 x 10^5

Therefore, the simplified expression in scientific notation is 1 x 10^5.
can you rewrite it with 4 steps instead?
Of course!

1. Multiply the coefficients: 5 * 2 = 10
2. Multiply the powers of 10: 10^6 * 10^-2 = 10^(6-2) = 10^4
3. Combine the coefficient and the power of 10: 10 * 10^4 = 1 * 10^5
4. Rewrite in scientific notation: 1 x 10^5

Therefore, the simplified expression in scientific notation is 1 x 10^5.